The A to Z of World War II the war against Japan - Wells, Anne Sharp (A to Z guides, 2009)
World War II dominates world history today as it dominated world attention over 60 years ago. In spite of the alliances that bound many of the same participants, the war was essentially two separate but simultaneous conflicts: one involved Japan as the major antagonist and took place mostly in Asia and Pacific; and the other, initiated by Germany and Italy, was contested mainly in Europe, North Africa, the Mediterranean, and the Atlantic. The A to Z of World War II: The War Against Japan traces the brutal conflict from Japan's seizure of Chinese territory in 1931, through the onset of war with the Western Allies in 1941, to the use of atomic weapons by the United States in 1945. It also addresses the aftermath of the war including the formation of the United Nations and the American occupation of Japan. As the first of two volumes covering World War II, this volume concentrates on the war in Asia and the Pacific so the user benefits from the comprehensive explanations of the people, places, and events that shaped much of that region's 20th-century history